A review on writings on religious tolerance in Malaysia - Ruhaizah Abdul Ghani; Jaffary Awang (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2017)
Living in a multi-religious and multi-cultural country like Malaysia is a very challenging experience. It requires understanding and cooperation among the races so as to ensure good relations. The race relations developed gradually and went through various stages throughout the history based on the political and the social circumstances of the society. Throughout the history, authors were inspired to write about the development of the race relation from one stage to the next until it proceeded to write about religious tolerance. This paper examines the writings on religious tolerance in Malaysian settings. By using the historical approach, it analyses the pattern of writings from the early stage of race relations to the evolvement of specific writings on religious tolerance. The issue of religious tolerance captured researchers’ and writers’ attention during the 2000s due to the incident of 11th September 2001 and the global phenomenon of Islamophobia which affected public perception of Islam and Muslims. The ill-informed public perception created discomfort among the different religions in Malaysia. At worst it could cause race conflicts. Hence, efforts were made by concerned authors to write regarding the issue with the aim of removing the prevalent prejudice and misconception about Islam and Muslims and to enhance religious tolerance as the vital element for sustaining good relations among the races.